Haiti : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper on Haiti examines the observed reduction in outstanding real bank credit to the private sector. It examines the evolution of credit and real GDP growth and uses demand and supply indicators to characterize the reduction in credit allocation to the private sector. The paper also provides an overview of the taxation system for the major petroleum products under the present fixed pricing policy and a hypothetical implementation of the 1995 law introducing a flexible pricing mechanism.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet